[4]Cyclo‐N‐ethyl‐2, 7‐carbazole: Synthesis, Structural, Electronic and Charge Transport Properties. Issue 32 (16th May 2019) - Lucas, Fabien; Sicard, Lambert; Jeannin, Olivier; Rault‐Berthelot, Joëlle; Jacques, Emmanuel; Quinton, Cassandre; Poriel, Cyril
Abstract: Nanorings, which are macrocycles possessing radially directed π‐orbitals have shown fantastic development in the last ten years. Unravelling their unusual electronic properties has been one of the driving forces of this research field. However, and despite promising properties, their incorporation in organic electronic devices remains very scarce. In this work, we aim to contribute to bridge the gap between organic electronics and nanorings by reporting the synthesis, the structural and electronic properties and the incorporation in an organic field‐effect transistor (OFET) of a cyclic tetracarbazole, namely [4]cyclo‐ N ‐ethyl‐2, 7‐carbazole ([4]C‐Et‐Cbz ). The structural, photophysical and electrochemical properties have been compared to those of structurally related analogues [4]cyclo‐9, 9‐diethyl‐2, 7‐fluorene [4]C‐diEt‐F (with carbon bridges) and [8]‐cycloparaphenylene [8]CPP (without any bridge) in order to shed light on the impact of the bridging in nanorings. This work shows that nanorings can be used as an active layer in an OFET and provides a first benchmark in term of OFET characteristics for this type of molecules. Abstract : Put a (nano)ring on it : We report the synthesis, structural and electronic properties and the incorporation in an organic field‐effect transistor of a cyclic tetracarbazole, namely [4]cyclo‐ N ‐ethyl‐2, 7‐carbazole.